On the identification of hyperhydrated sodium chloride hydrates, stable at icy moon conditions - Journaux, Baptiste; Pakhomova, Anna; Collings, Ines E.; Petitgirard, Sylvain; Boffa Ballaran, Tiziana; Brown, J. Michael; Vance, Steven D.; Chariton, Stella; Prakapenka, Vitali B.; Huang, Dongyang; Ott, Jason; Glazyrin, Konstantin; et al. (Proceedings of the National Academy of Sciences, 2023)
Sodium chloride is expected to be found on many of the surfaces of icy moons like Europa and Ganymede. However, spectral identification remains elusive as the known NaCl-bearing phases cannot match current observations, which require higher number of water of hydration. Working at relevant conditions for icy worlds, we report the characterization of three “hyperhydrated” sodium chloride (SC) hydrates, and refined two crystal structures [2NaCl·17H 2 O (SC8.5); NaCl·13H 2 O (SC13)]. We found that the dissociation of Na + and Cl − ions within these crystal lattices allows for the high incorporation of water molecules and thus explain their hyperhydration. This finding suggests that a great diversity of hyperhydrated crystalline phases of common salts might be found at similar conditions. Thermodynamic constraints indicate that SC8.5 is stable at room pressure below 235 K, and it could be the most abundant NaCl hydrate on icy moon surfaces like Europa, Titan, Ganymede, Callisto, Enceladus, or Ceres. The finding of these hyperhydrated structures represents a major update to the H 2 O–NaCl phase diagram. These hyperhydrated structures provide an explanation for the mismatch between the remote observations of the surface of Europa and Ganymede and previously available data on NaCl solids. It also underlines the urgent need for mineralogical exploration and spectral data on hyperhydrates at relevant conditions to help future icy world exploration by space missions.